2006
DOI: 10.1186/1477-3155-4-13
|View full text |Cite
|
Sign up to set email alerts
|

Truncated forms of viral VP2 proteins fused to EGFP assemble into fluorescent parvovirus-like particles

Abstract: Fluorescence correlation spectroscopy (FCS) monitors random movements of fluorescent molecules in solution, giving information about the number and the size of for example nanoparticles. The canine parvovirus VP2 structural protein as well as N-terminal deletion mutants of VP2 (-14, -23, and -40 amino acids) were fused to the C-terminus of the enhanced green fluorescent protein (EGFP). The proteins were produced in insect cells, purified, and analyzed by western blotting, confocal and electron microscopy as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Before further modifications of the location of SpT, we confirmed the VLP formation of the self-assembled SpT-VP2 in TEM ( Figure 1F ) and investigated the possible protein display by immuno-TEM using anti-His6 for SpC-EGFP ( Figure 1G ). The intact VLP structure and distribution (20–30 nm) were validated ( Figure 1H ) in this study, consistent with previous studies ( Choi et al, 2000 ; Gilbert et al, 2006 ). This result provides direct evidence that VP2-derived SpT-SpC partner can be successfully expressed in silkworm-BEVS and be realized as a VLP display system.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Before further modifications of the location of SpT, we confirmed the VLP formation of the self-assembled SpT-VP2 in TEM ( Figure 1F ) and investigated the possible protein display by immuno-TEM using anti-His6 for SpC-EGFP ( Figure 1G ). The intact VLP structure and distribution (20–30 nm) were validated ( Figure 1H ) in this study, consistent with previous studies ( Choi et al, 2000 ; Gilbert et al, 2006 ). This result provides direct evidence that VP2-derived SpT-SpC partner can be successfully expressed in silkworm-BEVS and be realized as a VLP display system.…”
Section: Resultssupporting
confidence: 92%
“…The VLP formation of CPV can be obtained via the self-assembly of capsid VP2 protein in various protein expression systems, including BEVS with cultured insect Sf9 cells, silkworm Bm5 cells, silkworm larvae, and pupae ( Choi et al, 2000 ; Feng et al, 2014 ; Jin et al, 2016 ; Chang et al, 2020 ). Previous literature has also found that the N-terminal genetically fused GFP can be used as a protein display strategy ( Gilbert et al, 2006 ). Thus, as a continuous effort for our previous SpyBEVS ( Xu et al, 2019 ), we designed several SpT-SpC chemistry constructs at terminal regions to establish protein display on CPV-LPs in silkworm-BEVS (SpyVLP-BEVS), which are illustrated in Figures 1A, B .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acid position 101, although also presenting a fixed substitution (I101T), was identified as being under negative selection pressure, probably due to the observed existence of two different triplets codifying for the same aa (data not shown). An interesting observation related to the tridimensional structure of VP2 is that positions 87, 101, and 555, although outside the GH loop, are in an exposed region of the protein [48,49].…”
Section: Discussionmentioning
confidence: 98%
“…The diffusion dynamics were examined using photoactivable GFP (PAGFP) fused N-terminally with the major capsid protein VP2. It is known that such a fusion allows for assembly of VLPs [49] . Also, in the case of another parvovirus, the minute virus of mice, the capsid proteins enter the nuclei only in trimeric form [50] .…”
Section: Discussionmentioning
confidence: 99%